Role of renal sympathetic nervous system in the control of renal potassium handling - Salman, I.M.; Sattar, M.A.; Abdullah, N.A.; Ameer, O.Z.; Basri, F.; Hussain, N.M.; Yam, M.F.; Swarup, K.R.L.A.; Rathore, H.A.; Kazi, R.N.; Khan, M.A.H.; Johns, E.J. (2010)
Background: It is well established that renal sympathetic nerves are primarily involved in renal sodium and water regulation. However, the relationship between renal sympathetic nerve activity (RSNA) and renal potassium handling is not extensively known. The present study was performed to investigate the role of the renal sympathetic nervous system in the regulation of tubular potassium reabsorption and secretion. Methods: Male Sprague Dawley (SD) rats (each group, n=6) were fasted overnight, anesthetized with pentobarbital sodium (60 mg/kg intraperitoneal), denervated by application of phenol to the left renal artery and maintained on an intravenous infusion of saline for 2 hours. During this period, 6 urine and plasma samples were collected at 20-minute intervals to study kidney function parameters. Results: In denervated rats, there were significantly higher (all p<0.05 vs. innervated control) urine flow rate (UFR), glomerular filtration rate (GFR), absolute sodium excretion (U(Na)V), fractional sodium excretion (FE(Na)), absolute potassium excretion (U(K)V), fractional potassium excretion (FE(K)) and urinary sodium to urinary potassium ratio (U(Na)/U(K)). No appreciable differences were seen in the mean arterial pressure (MAP) and plasma sodium (P(Na)) between denervated and innervated SD rats. However, plasma potassium (P(K)) levels were significantly lower (p<0.05) in denervated rats as compared with innervated counterparts. Conclusions: There is a possible involvement of renal nerves in the regulation of renal potassium handling. This effect is largely attributable to a direct action of renal sympathetic nerves on the renal tubular segments.